Platform comparison of detecting copy number variants with microarrays and whole-exome sequencing - de Ligt, Joep; Boone, Philip M.; Pfundt, Rolph; Vissers, Lisenka E.L.M.; de Leeuw, Nicole; Shaw, Christine; Brunner, Han G.; Lupski, James R.; Veltman, Joris A.; Hehir-Kwa, Jayne Y. (Genomics data, 2014)
Copy number variation (CNV) is a common source of genetic variation that has been implicated in many genomic disorders, Mendelian diseases, and common/complex traits. Genomic microarrays are often employed for CNV detection. More recently, whole-exome sequencing (WES) has enabled detection of clinically relevant point mutations and small insertion—deletion exome wide. We evaluated (de Ligt et al. 2013) [1] the utility of short-read WES (SOLiD 5500xl) to detect clinically relevant CNVs in DNA from 10 patients with intellectual disability and compared these results to data from three independent high-resolution microarray platforms. Calls made by the different platforms and detection software are available at dbVar under nstd84.